How universal are universal pre-school health and developmental screens? Evidence from New Zealand’s Integrated Data Infrastructure (IDI) - Audas, Richard (International Journal of Population Data Science, 2018)
In New Zealand, children participate in a pre-school screen to ensure they are reaching key developmental milestones and not having significant physical, emotional or behavioural issues. This pre-school screen is called the Before School Check (B4SC) and it is intended to be implemented after the child's fourth birthday and before they enter school, after their fifth birthday. If children fall short of key developmental milestones or have other health or behavioural issues, they may be referred to other services so that they these problems can be remediated prior to entry to primary school. In New Zealand, B4SC participation is high, with greater than 90% of the eligible population participating each year. However, the rates of completion are lower, with many children not completing all components. We speculate that non-participation in the B4SC, is concentrated among the most vulnerable of children – those who would most likely benefit from an intervention. In New Zealand, government collected administrative files, including the B4SC are housed in the Statistics New Zealand Integrated Data Infrastructure (IDI). We link B4SC records to a variety of data files, including health records, census and measures of residential mobility and find conventional risk factors significantly predict B4SC participation.